2020
DOI: 10.1186/s12935-020-01471-w
|View full text |Cite|
|
Sign up to set email alerts
|

A novel mechanism by which ACTA2-AS1 promotes cervical cancer progression: acting as a ceRNA of miR-143-3p to regulate SMAD3 expression

Abstract: Background: Long non-coding RNAs (LncRNAs) have been increasingly confirmed to be abnormally expressed in human cancer and closely related to tumorigenesis. LncRNA ACTA2-AS1 is abnormally expressed in multiple tumors and participates in their development. However, whether ACTA2-AS1 plays a role in the development of cervical cancer (CC) and the exact mechanism of its role has not been elucidated. Methods: Quantitative real-time PCR (qRT-PCR) was conducted to detect the expression level of messenger RNA of ACTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…In addition, ectopic expressions of lncRNAs lead to the abnormality of ceRNA regulatory network, in which lncRNAs competitively interact with miRNAs to regulate expression patterns of target genes, thus inducing carcinogenesis and cancer growth [ 18 ]. For example, lncRNA ACTA2-AS1 promotes cervical cancer development through serving as a ceRNA for miR-143-3p to upregulate SMAD3 expression [ 19 ]. Hence, the interaction between GATA6-AS1 and miR-4530 was to be explored in our study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ectopic expressions of lncRNAs lead to the abnormality of ceRNA regulatory network, in which lncRNAs competitively interact with miRNAs to regulate expression patterns of target genes, thus inducing carcinogenesis and cancer growth [ 18 ]. For example, lncRNA ACTA2-AS1 promotes cervical cancer development through serving as a ceRNA for miR-143-3p to upregulate SMAD3 expression [ 19 ]. Hence, the interaction between GATA6-AS1 and miR-4530 was to be explored in our study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that miR-143-3p regulates the expression of Smad3 in cervical cancer. 24 We found the binding site of miR-143-3p on Smad3…”
mentioning
confidence: 78%
“…Recently, it was reported that ACTA2-AS1 is significantly over-expressed in cervical cancer, upregulating SMAD3 expression by competitively sponging miR-143-3p [ 15 ]. However, ACTA2-AS1 may act as a tumor suppressor in lung adenocarcinoma and liver cancer cell via sequestering miR-378a-3p and miR-4428 to upregulate the expression of SOX7.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA ACTA2-AS1 (ACTA2 Antisense RNA 1) is located at 10q23.31 with five exons [ 12 ]. Recent studies revealed that dysregulation of ACTA2-AS1 has been found to be closely related to poor prognosis of several cancers, such as cervical cancer, hepatocellular carcinoma, liver cancer, breast cancer and lung adenocarcinoma [ 13 15 ]. According to previous studies, ACTA2-AS1 may play an important role involved in the development of human cancers.…”
Section: Introductionmentioning
confidence: 99%